Evaluation of Different Genetic Targets for Salmonella enterica Serovar Enteriditis and Typhimurium, Using Loop-Mediated Isothermal AMPlification for Detection in Food Samples - Azinheiro, Sarah; Carvalho, Joana; Prado, Marta; Garrido-Maestu, Alejandro (Frontiers in Sustainable Food Systems, 2018)
Salmonella Enteritidis and Salmonella Typhimurium continue to be the most frequently identified serovars among confirmed cases of salmonellosis. In the current study different genetic targets (safA, sdf I, STM4497 and typh) were compared, attending to their specificity and sensitivity in pure cultures and in spiked samples, in order to determine their capacity to accurately identify them by loop-mediated isothermal amplification (LAMP). For the genes selected to detect Enteritidis, both performed equally well regarding their specificity, but safA proved more sensitive than Sdf I; minor differences were observed among these genes when analyzing spiked food samples. Regarding the targets for Typhimurium, STM4497 and typh, the former demonstrated to be more specific and sensitive, both when analyzing pure cultures as well as spiked samples. These results highlight the importance of an adequate evaluation of the genetic targets selected, before their implementation for routine analyses.